2007
DOI: 10.1007/s00221-007-1062-5
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral ischemia induces transcription of inflammatory and extracellular-matrix-related genes in rat cerebral arteries

Abstract: Background and purpose -Cerebral ischemia results in a local inflammatory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 29 publications
(43 reference statements)
1
52
0
Order By: Relevance
“…The activity of AQP-4 and MMP-9 is influenced by numerous factors. Studies have indicated that damage to the central nervous system may activate the expression of MMP-9 and AQP-4 via the JNK pathway (5,6). JNK is a member of the mitogen-activated protein kinase (MAPK) family, which are involved in mediating the inflammatory response following cerebral ischemia, cell factors, cell proliferation and differentiation as well as the process of oxidant stress (5,6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The activity of AQP-4 and MMP-9 is influenced by numerous factors. Studies have indicated that damage to the central nervous system may activate the expression of MMP-9 and AQP-4 via the JNK pathway (5,6). JNK is a member of the mitogen-activated protein kinase (MAPK) family, which are involved in mediating the inflammatory response following cerebral ischemia, cell factors, cell proliferation and differentiation as well as the process of oxidant stress (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that damage to the central nervous system may activate the expression of MMP-9 and AQP-4 via the JNK pathway (5,6). JNK is a member of the mitogen-activated protein kinase (MAPK) family, which are involved in mediating the inflammatory response following cerebral ischemia, cell factors, cell proliferation and differentiation as well as the process of oxidant stress (5,6). The activation of JNK induces the phosphorylation of downstream factors, including c-Jun, protein 53 and activator protein 1, as well as modulating gene expression, protein synthesis and neuronal apoptosis (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arf3 is a ubiquitous class I ADP-ribosylation factor (Arf) protein that is mainly expressed in neural tissues [32]. Its down-regulation between 6 and 72 h after pMCAO may be a protective response in the acute phase preventing secretion of matrix metalloproteinase-9 [33], a metalloprotease that is responsible for the development of injury following brain insult [34,35], whereas, at the late phase, when its expression returns to control levels, Arf3 may promote neuronal differentiation and maturation [36], although further studies are required to confirm these hypotheses. Finally, Acsl4 is a member of the mammalian long-chain fatty acid-CoA ligases (Acsl) family, which plays an important role in arachidonic acid metabolism [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…After initial denaturation at 95°C for 30 s, the PCR cycle consisted of denaturation at 95°C for 5 s and annealing and elongation for 60°C for 45 s; 45 cycles was performed. The sequences of primers for TNFα, 23 interleukin-6 (IL-6), 24 inducible nitric oxide synthase (iNOS), 23 endothelial NO synthase (eNOS), cyclooxygenase 2 (COX2), 25 EP4, HAS2 and Toll-like receptor 4 (TLR4) 26 are listed in Table S1. The abundance of each gene was determined relative to an internal control using 18 s ribosomal RNA.…”
Section: Editorial P 601mentioning
confidence: 99%